The Supplement to the English Dialect Dictionary: Its Structure and Value as Part of EDD Online. (22nd November 2018) - Markus, Manfred
Abstract: This paper sheds light on the structure and lexicographic value of the Supplement of Joseph Wright's English Dialect Dictionary, published as part of the last volume in 1905. With its nearly 8, 000 entries, the Supplement amounts to ca. 11% of the complete dictionary. The present study, based on EDD Online, argues that the Supplement, apart from its quantity, is also a valuable addition to the dictionary proper for reasons of the quality of the entries. The analysis focuses on the questions of why Wright marked some of the entries of the Supplement as 'not sufficiently authorised' and others as more creditable. The final result of the study is that Wright was not only guided in his selection of reliable entries by the interpretation of his sources, but also by his competence and experience as a philologist and native dialect speaker.